1995
DOI: 10.1007/bf01499324
|View full text |Cite
|
Sign up to set email alerts
|

First-ballot votes, predeliberation dispositions, and final verdicts in jury trials.

Abstract: for their assistance in conducting the interviews; Steve McKinley and Professors Young Koh, Dualatram Lund and Alexander Weiss for their comments on the statistics, and the anonymous reviewers for the helpful suggestions. Copies of reprints can be obtained from either Maria Sandys,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 16 publications
5
65
0
Order By: Relevance
“…Broadly speaking, there have been two approaches to studying real jurors. In one approach, jurors are questioned about the trial in which they were involved after completing jury duty (e.g., Moran & Comfort, 1982;Reifman, Gusick, & Ellsworth, 1992;Sandys & Dillehay, 1995). Al-though this method has the drawback of potential memory bias in jurors' retrospective reports, it tends to support the fi ndings of simulation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, there have been two approaches to studying real jurors. In one approach, jurors are questioned about the trial in which they were involved after completing jury duty (e.g., Moran & Comfort, 1982;Reifman, Gusick, & Ellsworth, 1992;Sandys & Dillehay, 1995). Al-though this method has the drawback of potential memory bias in jurors' retrospective reports, it tends to support the fi ndings of simulation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, potential biases against the defendant resulting from overly emotional evidence might be attenuated after group deliberation (as found in laboratory research by Kaplan & Miller, 1977. Alternatively, deliberation might also maximize initial biases, or do little more than develop the picture that was formed before deliberation among the majority of jurors (Kalven & Zeisel, 1966;MacCoun & Kerr, 1988;Sandys & Dillehay, 1995; for a review, see Devine, Clayton, Dunford, Seying, & Pryce, 2001). Most of the research we reviewed considered individual jurors' judgments, and if emotional evidence causes more individual jurors to favor a punitive judgment before deliberation, then the chance is increased that the pre-deliberation picture, which deliberation might develop, is one that is biased toward a more punitive decision.…”
Section: Caveatsmentioning
confidence: 93%
“…Also, our mock jurors did not deliberate as a group, which might attenuate (Shaw & Skolnick, 1995) or amplify (Moscovici & Zavalloni, 1969) individual jurors' biases. Yet several studies (including one using a case involving a juvenile defendant, Haegerich & Bottoms, 2004) have found that deliberation has few effects on postdeliberation verdicts as compared with the average of pre-deliberation verdict preferences (Kalven & Zeisel, 1966;MacCoun & Kerr, 1988;Sandys & Dillehay, 1995).…”
Section: Caveats and Implicationsmentioning
confidence: 97%